Using a weblog as an ePortfolio tool in elementary school essay writing - Iolie Nicolaidou (My University, 2010)
This empirical, quantitative, multiple case-study explored the development of students' writing performance through a one-academic-year (September 2007 to June 2008) implementation of learning portfolios in three fourth grade elementary school classes (N = 63 students) in Cyprus. It explored how learning portfolio affordances, such as feedback, goal-setting, reflection and self-evaluation related to students' writing performance over time. From a technological perspective, the challenge of the lack of availability of a portfolio tool in the Greek language was faced. The solution was a generic, open-source weblog tool (specifically WordPress), which was transformed and localized into Greek to be used as an ePortfolio tool. The students of one fourth grade class created ePortfolios (n1 = 20) while the students of another two fourth grade classes (n2 = 23, n3 = 20) created paper-based portfolios. A portfolio artifact analysis focused on a total of 514 student-essays, 2822 instances of peer feedback, 3346 instances of teacher feedback, 477 goals, 308 self-evaluations and 162 reflections. The analysis of students' pre- and postimplementation writing performance tests, and the portfolio artifact analysis revealed that students' writing performance increased over time (t (62) = -14.19, p<,.05, n, = 0.77). These learning gains were associated with specific portfolio affordances. The findings of this study regarding the relation of portfolios with students' writing performance are of interest to education researchers. The study also produced practical implications on portfolio implementation that are of interest to teachers. It showed that most features currently implemented in ePortfolio tools can be supported in a weblog environment and demonstrated the feasibility and effectiveness of this idea in the elementary school context. The described open-source weblog ePortfolio tool can be used in different languages providing easy access to free portfolio tools for elementary schools worldwide.
Keywords: Students; Reflection; Social networking (online); Teaching; E-portfolios; Elementary schools; Elementary-school; Learning portfolio; Post-implementation; Technological perspective; Weblog; Writing-performance